Treatment approaches of central auditory processing deficit - Sladjana Calasan; Sofija Bajagić; Branislava Ćurčić (Биомедицинска истраживања, 2024)
Central auditory processing disorder (CAPD) disrupts the brain ability to interpret sound signals despite normal peripheral hearing function. This article aims to identify and analyze various treatment approaches, which are used in the treatment of CAPD and to provide an overview of available empirical evidence on the effectiveness of these approaches. Google Scholar, PubMed and Research Gate were used for literature Reviews. Treatment approaches vary and depend on the individual characteristics of children themselves, and one of the most commonly used approaches in the treatment is auditory training, through which children learn to identify and discriminate auditory stimuli. Apart from choosing the appropriate approach, it is crucial to commence the treatment of children with central auditory processing deficit in time in order to overcome and eliminate this deficit.
Keywords: auditory processing; auditory processing disorder; auditory training